The Fate of EMRI-IMRI Pairs in Active Galactic Nucleus Accretion Disks: Hydrodynamical and Three-body Simulations - Peng Peng; Alessia Franchini; Matteo Bonetti; Alberto Sesana; Xian Chen (The Astrophysical Journal)
Extreme-mass-ratio inspirals (EMRIs) and intermediate-mass-ratio inspirals (IMRIs) are important gravitational wave (GW) sources for the Laser Interferometer Space Antenna. It has recently been suggested that EMRIs and IMRIs can both form in the accretion disk of an active galactic nucleus (AGN). Considering the likely encounter between a stellar-mass black hole (sBH) and an intermediate-mass black hole (IMBH) during migration in the AGN disk, P. Peng & X. Chen (Paper I) showed that a gap-opening IMBH can drive a surrounding sBH to migrate synchronously. In this work, we extend the study in Paper I with a more sophisticated model. We first use 3D hydrodynamical simulations to study the coevolution of the disk and the migration of an sBH in the vicinity of an IMBH. We find that the gaseous torque, together with the tidal torque exerted by the IMBH, can drive synchronized migration until ∼10 Schwarzschild radii from the central supermassive black hole. We further use a relativistic three-body code to study the final fate of the sBH in the GW-dominated regime. We find that the sBH can be either captured or kicked out by the IMBH, which will result in either two subsequent IMRIs or an EMRI followed by an IMRI. These events will bring rich information about the formation and evolution of sBHs and IMBHs in AGNs.